Childhood acute poisoning in the Italian North-West area: a six-year retrospective study - Giovanni N. Berta; Federica Di Scipio; Francesca M. Bosetti; Barbara Mognetti; Federica Romano; Maria E. Carere; Anna C. Del Giudice; Emanuele Castagno; Claudia Bondone; Antonio F. Urbino (BMC, 2020)
Abstract Background Data about acute poisoning in Italian pediatric patients are obsolete or absent. This study would partially fill this exiting gap and compare the scene with others around the world. Methods A retrospective evaluation was performed on a 2012-2017 data registry of the Children's Emergency Department at the Regina Margherita Hospital of Turin, where 1030 children under age 14 were accepted with a diagnosis of acute intoxication. Results The median age of the patients was 2.2 years (IQR 2.3) and 55% were male. Events occurred mostly in children aged 1-4 years (n = 751, 72.9%). Six hundred and eight patients (59%) were exposed to Nonpharmaceutical agents, the household cleaning products being the more frequent (n = 298, 49%). Exposure to Pharmaceuticals were 422 (41%); the most common Pharmaceuticals were analgesics (n = 88, 20.8%), psychotropics (n = 77, 18.2%) and cardiovascular (n = 53, 12.6%) drugs. The 85% of the intoxications occurred accidentally, the 10.6% as therapeutic error, the 2.3% as suicide attempts and the 1.5% for recreational purposes. No patient died. Conclusions Despite acute poisoning being a relevant problem in pediatric emergency, our results would seem to paint a less worrying picture if compared to other countries, mainly when considering the children hospitalized in the pediatric intensive care unit and the number of deaths. Nevertheless, our study might represent a tool for public health authorities to program incisive interventions.